Effects of posture on the distribution of pulmonary ventilation and perfusion in children and adults. Issue 6 (June 1989) - Bhuyan, U; Peters, A M; Gordon, I; Davies, H; Helms, P
Abstract : In the adult the distributions of ventilation and of perfusion show the same directional dependence on gravity. In children, however, the distribution of ventilation in response to gravity is the reverse of that seen in adults. The aim of the current study was to determine whether perfusion showed the same reversal in children or followed the adult pattern. Distribution of perfusion was measured with intravenous technetium-99m macroaggregated albumin and distribution of ventilation with inhaled krypton-81m. Eighteen children and seven adults were studied; they had been referred for lung scanning for various respiratory problems. The effect of gravity was examined by giving aliquots of macroaggregated albumin and 81mKr by inhalation to the subject in the supine and the lateral decubitus position. Counts in the dependent lung were compared with those in the upper lung. The dependent lung in the lateral decubitus position received more of the total perfusion than it did in the supine position in seven children with a normal chest radiograph (mean 7.0%, range 4.8-10.9% more) and in 11 children with an abnormal radiograph (mean 3.4%(0.1-10.0%)). Ventilation, however, changed in the opposite direction, falling by 7.1% (-3.2% to -12.8%) in five children with a normal chest radiograph and 11.2% (-2.8% to -19.3%) in eight children with an abnormal radiograph. Fractional V/fractional Q (an index of the ventilation:perfusion ratio) decreased in the dependent lung in the children when they moved from the supine to the decubitus position. The same directional change was recorded in adults, but it was significantly less than in the children, irrespective of whether the chest radiograph was abnormal. In children and adults with various respiratory problems the effect of posture on the distribution of perfusion is similar.